To What Extent Do Workplace Relationships, Financial Rewards, and Recognition Shape Employee Work-Life Satisfaction in Islamic Bank? - Puspitasar, Yunita Dwi; Nur Azizah, Siti (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze the impact of workplace relationships, financial rewards, and appreciation on the work-life satisfaction of employees at Bank BJB Syariah, Bekasi Branch. The research background is based on issues of job dissatisfaction, which affect motivation and productivity and ultimately influence employees' overall work-life satisfaction. Additionally, the increasing employee turnover rate at Bank BJB Syariah from 2020 to 2022 has become a concern. A quantitative research method was employed, with data analyzed using SPSS 27. The findings indicate that workplace relationships and financial rewards have a significant impact on employees' work-life satisfaction, while appreciation does not exert a significant influence on employee satisfaction at Bank BJB Syariah, Bekasi Branch. These findings highlight that employee relationships and financial rewards play a more significant role than appreciation in enhancing work-life satisfaction.This study contributes to a deeper understanding of the factors affecting work-life satisfaction in the Islamic banking sector and provides insights for formulating strategies to enhance employee well-being.